Electrolyte composition, electrolyte sheet and secondary battery
By incorporating garnet-type oxides with a specific particle size and an ionic liquid with imidazolium cations and sulfonylimide anions, along with a vinylidene fluoride-based binder and aprotic/protic polar solvents, the electrolyte composition effectively reduces gelation and enhances the performance of secondary batteries.
Patent Information
- Application Number
- JP2021077374
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-04-30
AI Technical Summary
Garnet-type oxides containing Li, La, and Zr in existing electrolyte compositions tend to be basic, leading to gelation when dispersed with organic compounds, which prevents the formation of a moldable electrolyte sheet and affects the performance of secondary batteries.
The electrolyte composition includes garnet-type oxides with a particle diameter of 1.4 μm or more, an ionic liquid with imidazolium cations and sulfonylimide anions, a binder containing vinylidene fluoride, and a solvent that is a combination of aprotic and protic polar solvents, which reduces the basicity of the oxide and minimizes gelation.
This approach reduces gelation, stabilizes the dispersion state of components, and enhances the performance of the electrolyte sheet and secondary batteries by maintaining the ionic conductivity and mechanical strength of the electrolyte layer.
Smart Images

Figure 0007666984000003 
Figure 0007666984000004 
Figure 0007666984000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolyte composition, an electrolyte sheet, and a secondary battery. [Background technology]
[0002] An electrolyte composition containing an oxide having a garnet structure containing Li, La, and Zr, an electrolyte salt, an ionic liquid, a binder, and a solvent is known (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6682708 Summary of the Invention [Problem to be solved by the invention]
[0004] In the prior art, the oxides having a garnet structure containing Li, La, and Zr are basic, so that the electrolyte composition in which the oxides and organic compounds are dispersed may gel (become non-fluid). When the electrolyte composition gels, the dispersion state of the components of the electrolyte composition becomes uneven, and the sheet cannot be molded.
[0005] The present invention has been made to solve this problem, and an object of the present invention is to provide an electrolyte composition, an electrolyte sheet, and a secondary battery that can reduce gelation. [Means for solving the problem]
[0006] To achieve this object, the electrolyte composition of the present invention includes an oxide having a garnet structure containing Li, La, and Zr, an electrolyte salt, an ionic liquid, a binder, and a solvent. The oxide has a particle size of 1.4 μm or more at which the cumulative frequency in a volumetric particle size distribution is 10%, and the ionic liquid includes an imidazolium cation and a sulfonylimide anion. The solvent is an aprotic and protophobic polar solvent, and the binder includes -CH2CF2-.
[0007] The electrolyte sheet of the present invention is made of an electrolyte composition. The secondary battery of the present invention includes a positive electrode layer, an electrolyte layer, and a negative electrode layer in this order, and at least one of the positive electrode layer, the electrolyte layer, and the negative electrode layer includes the electrolyte composition. Effect of the Invention
[0008] According to the electrolyte composition of the present invention, the basicity of the oxide is weakened, and interactions between the components are less likely to occur, thereby reducing gelation. An electrolyte sheet and a secondary battery containing the electrolyte composition can reduce variation in the dispersion state of the components. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view of a secondary battery according to an embodiment. [Diagram 2] 1 is an example of an integrated distribution of oxides. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Fig. 1 is a schematic cross-sectional view of a secondary battery 10 in one embodiment. The secondary battery 10 in this embodiment is a lithium ion solid-state battery in which the power generating element is made of a solid. The power generating element being made of a solid means that the skeleton of the power generating element is made of a solid, and does not exclude, for example, a form in which the skeleton is impregnated with a liquid.
[0011] 1, the secondary battery 10 includes, in order, a positive electrode layer 11, an electrolyte layer 14, and a negative electrode layer 15. The positive electrode layer 11, the electrolyte layer 14, and the negative electrode layer 15 are housed in a case (not shown).
[0012] The positive electrode layer 11 is formed by stacking a current collecting layer 12 and a composite layer 13. The current collecting layer 12 is a conductive member. Examples of the material for the current collecting layer 12 include a metal selected from Ni, Ti, Fe, and Al, an alloy containing two or more of these elements, stainless steel, and a carbon material.
[0013] The composite layer 13 contains an active material 19 and an electrolyte composition (described later). The electrolyte composition contains an oxide 18 having ion conductivity. In order to reduce the resistance of the composite layer 13, the composite layer 13 may contain a conductive additive. Examples of the conductive additive include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag.
[0014] The active material 19 is exemplified by a metal oxide having a transition metal, a sulfur-based active material, and an organic active material. The metal oxide having a transition metal is exemplified by a metal oxide containing Li and one or more elements selected from Mn, Co, Ni, Fe, Cr, and V. The metal oxide having a transition metal is exemplified by LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMn2O4, LiNiVO4, LiNi 0.5 Mn 1.5 O4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 Examples include O4 and LiFePO4.
[0015] In order to suppress the reaction between the active material 19 and the oxide 18, a coating layer can be provided on the surface of the active material 19. The coating layer is made of Al2O3, ZrO2, LiNbO3, Li4Ti5O 12 , LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4 and Li2MoO4 are examples.
[0016] Examples of sulfur-based active materials include S, TiS2, NiS, FeS2, Li2S, MoS3, and sulfur-carbon composites. Examples of organic active materials include radical compounds such as 2,2,6,6-tetramethylpiperidinoxyl-4-yl methacrylate and polytetramethylpiperidinoxyl vinyl ether, quinone compounds, radialene compounds, tetracyaquinodimethane, and phenazine oxide.
[0017] The electrolyte layer 14 is made of an electrolyte composition. The electrolyte composition includes an oxide 18, an electrolyte solution, and a binder. The oxide 18 is a solid electrolyte having a garnet structure and lithium ion conductivity, containing Li, La, Zr, and O. The basic composition of the oxide with the garnet structure is Li5La3M2O 12 (M=Nb, Ta). Oxide 18 is Li7La3Zr2O, in which the pentavalent M cations in the basic composition are replaced with tetravalent cations. 12 Examples include:
[0018] The oxide 18 may contain at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, V, Ga, Sr, Y, Nb, Sn, Sb, Ba, Hf, Ta, W, Bi, Rb, and lanthanides (excluding La) in addition to Li, La, and Zr. For example, Li6La3Zr 1.5 W 0.5 O 12 ,Li 6.15 La3Zr 1.75 Ta 0.25 Al 0.2 O 12 ,Li 6.15 La3Zr 1.75 Ta 0.25 Ga 0.2 O 12 ,Li 6.25 La3Zr2Ga 0.25 O 12 ,Li 6.4 La3Zr 1.4 Ta 0.6 O 12 ,Li 6.5 La3Zr 1.75 Te 0.25 O 12 ,Li 6.75 La3Zr1.75 Nb 0.25 O 12 ,Li 6.9 La3Zr 1.675 Ta 0.289 Bi 0.036 O 12 ,Li 6.46 Ga 0.23 La3Zr 1.85 Y 0.15 O 12 ,Li 6.8 La 2.95 Ca 0.05 Zr 1.75 Nb 0.25 O 12 ,Li 7.05 La 3.00 Zr 1.95 Gd 0.05 O 12 ,Li 6.20 Ba 0.30 La 2.95 Rb 0.05 ZrO 12 Examples include:
[0019] The oxide 18 has, for example, a cubic crystal structure (space group Ia-3d (- indicates an overline meaning a reversal operation), JCPDS: 84-1753). The oxide 18 preferably contains at least one of Mg and element A (A is at least one element selected from the group consisting of Ca, Sr, and Ba), with the molar ratio of each element satisfying all of the following (1) to (3), or contains both Mg and element A, with the molar ratio of each element satisfying all of the following (4) to (6). The element A is preferably Sr in order to increase the ionic conductivity of the oxide 18. (1) 1.33≦Li / (La+A)≦3 (2) 0≦Mg / (La+A)≦0.5 (3) 0≦A / (La+A)≦0.67 (4) 2.0≦Li / (La+A)≦2.5 (5) 0.01≦Mg / (La+A)≦0.14 (6) 0.04≦A / (La+A)≦0.17.
[0020] The oxide 18 is the particle size at which the cumulative frequency in the volume-based particle size distribution is 10% (hereinafter referred to as "D 10 The oxide 18 is a powder with a particle size of 1.4 μm or more. The volumetric particle size distribution of the oxide 18 is measured by a laser diffraction / scattering particle size distribution measuring device (e.g., Microtrac MT3300EX II). The sample used for measuring the particle size distribution is, for example, the oxide 18 as it is taken out from the electrolyte layer 14. An appropriate amount of the sample is placed in a solvent (0.2 wt% sodium hexametaphosphate aqueous solution), dispersed for 3 minutes using an ultrasonic disperser (e.g., SD-600 manufactured by Nippon Seiki Seisakusho), and then set in the measuring device. When calculating the particle size distribution, the sample refractive index is set to 1.81, and the solvent refractive index is set to 1.33.
[0021] FIG. 2 is an example of an integrated distribution (under sieve) showing the integrated value of the frequency in the volume-based particle size distribution of oxide 18. FIG. 2 shows the particle diameter D where the ratio of particles below this value is 10%. 10 The solid electrolyte (oxide) with a garnet structure containing Li, La, and Zr is strongly alkaline. In particular, oxide particles 18 with a small particle size and a large specific surface area are poor in chemical stability and are strongly alkaline. When the ratio of particles with a small particle size decreases, the chemical stability of oxide 18 increases and the basicity weakens. D of oxide 18 10 When the thickness is 1.4 μm or more, this tendency becomes remarkable.
[0022] The thickness of the electrolyte layer 14 containing the oxide 18 is determined by, for example, the particle diameter at which the integrated value of the frequency in the particle size distribution is 100% (hereinafter, “D 100 This is to prevent short circuits between the electrodes. Therefore, the D 10 The oxide 18 D is preferably less than 5 μm. 10 If is 5μm or more, D 100 As the electrolyte layer 14 becomes thicker, the amount of active material 19 per unit volume of the secondary battery 10 decreases, and the discharge capacity of the secondary battery 10 decreases. In order to ensure the discharge capacity of the secondary battery 10, the D 10 It is preferable that the thickness is less than 5 μm.
[0023] D 10 An example of a method for producing the oxide 18 having a particle size of 1.4 μm or more will be described. For example, the method for producing the oxide 18 includes a blending step of blending raw materials to obtain a blended material, a firing step of firing the blended material, and a heat treatment step of heating the obtained composite powder.
[0024] In the blending step, materials containing the elements that constitute the oxide 18 are blended to obtain a blended material. Examples of the materials include oxides, composite oxides, hydroxides, carbonates, chlorides, sulfates, nitrates, and phosphates that contain the elements Li, La, Zr, Mg, and A (A is at least one element selected from the group consisting of Ca, Sr, and Ba). The materials are pulverized and mixed to obtain the blended material.
[0025] It is preferable to include a calcination step between the blending step and the firing step, in which the blended material is calcined at 900-1100°C for 2-15 hours to obtain a calcined material. By passing through the calcination step, it becomes easier to obtain a garnet-type crystal structure after the firing step.
[0026] It is preferable to include a step of pulverizing and mixing the calcined material between the calcination step and the firing step. In this step, the calcined material is pulverized and mixed to obtain a mixed material. By passing through the step of pulverizing and mixing the calcined material, a uniform crystal phase is easily obtained after the firing step. The calcined material to which a binder has been added may be pulverized and mixed. Examples of the binder include methyl cellulose, ethyl cellulose, polyvinyl alcohol, and polyvinyl butyral.
[0027] In the sintering process, the compounded, calcined or mixed materials are molded, and then the molded body is sintered at, for example, 1000-1250°C for 3-36 hours to obtain a sintered body. The sintered body is crushed in an inert gas atmosphere to obtain a synthetic powder.
[0028] In the heat treatment process, the synthetic powder is placed in a furnace where gas flows in and out, and is heated in an atmosphere where the gas flows around the synthetic powder. The synthetic powder reacts with CO2 in the air, forming a Li2CO3 film on the surface of the synthetic powder, and the heat treatment causes the CO2 to be desorbed from the Li2CO3 film, and the structure of the synthetic powder is modified to obtain oxide 18. Examples of the temperature and time of the heat treatment include holding the temperature at 640°C or higher for 10 hours or more, and holding the temperature at 670°C or higher for 2 hours or more.
[0029] The gas is at least one selected from an inert gas and oxygen gas. The inert gas is not particularly limited as long as it is a gas that does not chemically react with the synthetic powder. Examples of the inert gas include nitrogen, helium, neon, argon, krypton, xenon, and radon. In particular, at least one selected from nitrogen, helium, and argon is preferable.
[0030] The inflow and outflow of the gas may be continuous or intermittent. The flow rate of the gas introduced into the furnace continuously or intermittently, and the period of the gas introduced intermittently are appropriately set according to the volume of the furnace and the mass of the synthetic powder. The CO2 concentration of the gas introduced into the furnace depends on the temperature of the heat treatment, but is preferably a concentration lower than the CO2 concentration in the atmosphere (380 ppm), for example, 100 ppm (volume) or less. The dew point of the gas introduced into the furnace is preferably -40°C or less, particularly -50°C or less. This is to promote the desorption of CO2 from the synthetic powder. The oxide 18 after the heat treatment is immediately mixed with an organic compound or the like and formed into a sheet, and the composite layers 13, 17 and the electrolyte layer 14 are obtained.
[0031] The median diameter of the circle-equivalent diameter of the oxide 18 appearing in the cross section of the electrolyte layer 14 is preferably 4 to 10 μm, more preferably 4 to 6 μm, in order to make the surface area of the oxide 18 appropriately large and to ensure the amount of lithium ions moving between the oxide 18 and the electrolyte present on the surface of the oxide 18.
[0032] To determine the median diameter of the oxide 18, first, a scanning electron microscope (SEM) image of the oxide 18 appearing on the cross section of the electrolyte layer 14 (a polished surface, a surface obtained by irradiating with a focused ion beam (FIB), or a surface obtained by ion milling) is analyzed, and the circle equivalent diameter is calculated from the area of each particle of the oxide 18 to determine the volumetric particle size distribution. The median diameter is the circle equivalent diameter at which the cumulative frequency in the particle size distribution is 50%. To ensure accuracy, the image for determining the particle size distribution is taken from a 400 μm area of the electrolyte layer 14. 2 The area shall be greater than or equal to the above.
[0033] The electrolyte solution contained in the electrolyte layer 14 includes an ionic liquid in which an electrolyte salt is dissolved. The ionic liquid is a compound consisting of a cation and an anion, and is liquid at room temperature and normal pressure. Since the ionic liquid constitutes the electrolyte solution, the flame retardancy of the electrolyte solution can be improved. Various physical properties and functions of the electrolyte solution are determined by the types and salt concentrations of the electrolyte salt and ionic liquid.
[0034] The electrolyte salt is a compound used for transferring cations between the positive electrode layer 11 and the negative electrode layer 15. The electrolyte salt is, for example, a lithium salt. The anion of the electrolyte salt is a halide ion (I - ,Cl - ,Br - etc.), SCN - ,BF4 - ,BF3(CF3) - ,BF3(C2F5) - ,PF6 - ,ClO4 - ,SbF6 - ,N(SO2F)2 - ,N(SO2CF3)2 - ,N(SO2C2F5)2 - ,B(C6H5)4 - ,B(O2C2H4)2 - ,C(SO2F)3 - ,C(SO2CF3)3 - ,CF3COO - ,CF3SO2O - ,C6F5SO2O - ,B(O2C2O2)2 - ,RCOO -(R is an alkyl group having 1 to 4 carbon atoms, a phenyl group, or a naphthyl group).
[0035] The anion of the electrolyte salt is N(SO2F)2, which has a sulfonyl group -S(=O)2-. - ,N(SO2CF3)2 - ,N(SO2C2F5)2 - Sulfonylimides such as N(SO2F)2 are preferred. The sulfonylimide anion is less susceptible to the increase in viscosity of the electrolyte and the decrease in ionic conductivity even when the salt concentration is high, and furthermore, it forms a highly stable and low-resistance coating (SEI), which reduces the reductive decomposition of the electrolyte and expands the reduction-side potential window. - The abbreviation is [FSI] - : It is called bis(fluorosulfonyl)imide anion, N(SO2CF3)2 - abbreviated as [TFSI] - : It is sometimes called bis(trifluoromethanesulfonyl)imide anion.
[0036] The ionic liquid is preferably one having imidazolium as a cationic species. The imidazolium cation is, for example, a compound represented by formula (1).
[0037] [ka]
[0038] In formula (1), R 1 -R 5 R each independently represents a hydrogen atom or an alkyl group. The alkyl group may have a substituent. 1 -R 5 The number of carbon atoms in the alkyl group (including the substituent) represented by the following formula is preferably 1 to 10, more preferably 1 to 5, and further preferably 1 to 4. This is to ensure the ionic conductivity of the electrolyte.
[0039] The substituent is not particularly limited. Examples of the substituent include an alkyl group, a cycloalkyl group, an aryl group, a hydroxyl group, a carboxyl group, a nitro group, a trifluoromethyl group, an amide group, a carbamoyl group, an ester group, a carbonyloxy group, a cyano group, a halogeno group, an alkoxy group, an aryloxy group, and a sulfonamide group.
[0040] The anion species of the ionic liquid is preferably a sulfonylimide. The sulfonylimide anion is N(SO2F)2 - ,N(SO2CF3)2 - ,N(SO2C2F5)2 - ,N(SO2C4F9)2 - Examples of the ionic liquid include 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMI-TFSI). An ionic liquid (electrolyte) containing an imidazolium cation and a sulfonylimide anion and having an electrolyte salt dissolved therein is preferred because it can ensure high ionic conductivity.
[0041] The binder contained in the electrolyte layer 14 binds the oxide 18. The binder contains a vinylidene fluoride-based polymer containing -CH2CF2-. This is because vinylidene fluoride-based polymers have high mechanical strength. There are no particular limitations on the vinylidene fluoride-based polymer as long as it contains -CH2CF2-. Examples of the vinylidene fluoride-based polymer include a homopolymer of vinylidene fluoride and a copolymer of vinylidene fluoride and a copolymerizable monomer.
[0042] The copolymerizable monomer may be a halogen-containing monomer (excluding vinylidene fluoride) or a non-halogen copolymerizable monomer. The halogen-containing monomer may be a chlorine-containing monomer such as vinyl chloride; a fluorine-containing monomer such as trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, or a perfluoroalkyl vinyl ether. The non-halogen copolymerizable monomer may be an olefin such as ethylene or propylene; an acrylic monomer such as acrylic acid, methacrylic acid, or an ester or salt thereof; or a vinyl monomer such as acrylonitrile, vinyl acetate, or styrene. One or more of the copolymerizable monomers are polymerized with vinylidene fluoride to form a copolymer.
[0043] The binder may contain other polymers than the vinylidene fluoride polymer. The content of the vinylidene fluoride polymer in the binder is, for example, 80-100% by mass. Examples of other polymers include fluorinated resins (excluding vinylidene fluoride polymers), polyolefins, rubber-like polymers such as styrene butadiene rubber, polyimides, polyvinylpyrrolidone, polyvinyl alcohol, and cellulose ethers. Examples of the fluorinated resins include fully fluorinated resins, partially fluorinated resins, and fluorinated resin copolymers. An example of the fully fluorinated resin is polytetrafluoroethylene. Examples of the partially fluorinated resins are polychlorotrifluoroethylene and polyvinyl fluoride. Examples of the fluorinated resin copolymers include tetrafluoroethylene-perfluoroalkylvinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, and ethylene-chlorotrifluoroethylene copolymers.
[0044] The electrolyte composition contains a solvent that dissolves the binder. The electrolyte salt also dissolves in the solvent. The solvent is aprotic and protophobic polar solvent. The classification of solvents (aprotic and protophobic) follows IM Kolthoff, Anal. Chem. 46,1992(1974). In Kolthoff's classification, solvents are broadly divided into "amphoteric" that have both acidity and basicity and can donate and accept protons, and "aprotic" that do not have hydrogen atoms that can form hydrogen bonds, and the latter are further divided into "protophilic" that are strongly basic and easily solvate with cations, and "protophilic" that are weakly basic and difficult to solvate with cations.
[0045] In aprotic and protophobic polar solvents, protons and hydrogen bonds hardly contribute to the reaction, and the oxide 18 is easily dispersed. Examples of aprotic and protophobic polar solvents include propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, sulfolane, acetonitrile, acetone, isobutyl methyl ketone, nitromethane, methyl ethyl ketone, and tetramethylsilane. The electrolyte composition contains one or more of these polar solvents.
[0046] The water content of the solvent or ionic liquid is preferably 200 ppm or less, more preferably 100 ppm or less, and particularly preferably 10 ppm or less, in order to reduce the reaction between the water contained in the solvent or ionic liquid and the oxide 18.
[0047] The electrolyte layer 14 is obtained by forming an electrolyte composition containing an oxide 18, an electrolyte salt, an ionic liquid, a binder, and a solvent into a sheet shape. At least a part of the solvent contained in the electrolyte composition is vaporized by drying under reduced pressure after forming the sheet to obtain the electrolyte layer 14, and disappears from the electrolyte layer 14. The type and amount of the solvent remaining in the electrolyte layer 14 are determined by gas chromatography-mass spectrometry (GC-MS).
[0048] The presumed mechanism by which an electrolyte composition with an organic compound dispersed therein gels (becomes non-fluid) is as follows. First, a small amount of moisture contained in the electrolyte composition reacts with a basic oxide with a garnet structure that contains Li, La, and Zr, producing LiOH and Li2O3 on the surface of the oxide. This causes the OH - increases and the basicity becomes stronger.
[0049] When hydrogen is bonded to the carbon atom at the 2nd position of the imidazolium cation in an ionic liquid, the ionic conductivity of the electrolyte decreases when the proton at the 2nd position is eliminated by a base. The proton eliminated from the imidazolium cation is OH - It reacts with the oxide to generate water. As mentioned above, the water generated reacts with the oxide to further increase its basicity.
[0050] Under basic conditions, vinylidene fluoride-based polymers in the binder are prone to forming polyene structures due to the desorption of HF. The polyene structure of vinylidene fluoride-based polymers causes the electrolyte composition to gel. Furthermore, an unintended SEI is formed due to an electrochemical reaction caused by the desorbed HF, and the resistance of the SEI increases.
[0051] In contrast, D 10 Since the oxide 18 having a diameter of 1.4 μm or more has a weak basicity, the reaction between the moisture contained in the electrolyte composition and the oxide 18 can be reduced. Since the basicity in the system is unlikely to become strong, the proton at the second position of the imidazolium cation is unlikely to be eliminated, and the decrease in the ionic conductivity of the electrolyte solution caused by the elimination of the proton is reduced. Furthermore, the polar solvent contained in the electrolyte composition hardly contributes to the reaction through protons or hydrogen bonds, and the vinylidene fluoride-based polymer is unlikely to be polyenized due to the elimination of HF, so gelation of the electrolyte composition is reduced. Furthermore, since the electrochemical reaction caused by HF is unlikely to occur, the resistance of the SEI can be kept low.
[0052] In the electrolyte layer 14 (electrolyte composition), the content (volume %) of the ionic liquid with respect to the total amount of the oxide 18 and the ionic liquid is preferably 50% by volume or less (excluding 0% by volume). That is, oxide:ionic liquid = (100 - X):X, where 0 < X ≤ 50. This is to reduce the occurrence of bleeding of the ionic liquid while ensuring ionic conductivity by the ionic liquid interposed between the oxides 18.
[0053] The content (volume %) of the ionic liquid is determined by freezing the electrolyte layer 14 or embedding and solidifying the electrolyte layer 14 in a tetrafunctional epoxy resin or the like, and then analyzing a 5000-fold field of view randomly selected from the cross-section of the electrolyte layer 14 using a SEM equipped with an energy dispersive X-ray spectrometer (EDS). The analysis is performed by specifying the distribution of La, Zr, and S or analyzing the contrast of the backscattered electron image by image analysis to specify the area of the oxide 18 and the area of the ionic liquid, and regarding the ratio of the area in the cross-section of the electrolyte layer 14 as the ratio of the volume in the electrolyte layer 14 to obtain the content (volume %) of the ionic liquid.
[0054] The lithium ion conductivity of the electrolyte composition is determined by the types of the oxide 18, the electrolyte salt, and the ionic liquid, the salt concentration, etc. The lithium ion conductivity of the electrolyte composition at 25°C is preferably 4.0×10 -5 S / cm or more. This is to ensure the output density of the secondary battery 10 including the electrolyte composition.
[0055] Since the electrolyte composition contains anions derived from the electrolyte solution, the lithium ion conductivity of the electrolyte composition is calculated by multiplying the total ion conductivity calculated by the alternating current impedance method of a symmetric cell in which current collectors are adhered to both sides of the electrolyte composition formed in a sheet shape by the transport number of lithium ions. The transport number of lithium ions is determined by the alternating current impedance method and the steady state direct current method.
[0056] The transport number is calculated as follows. First, the resistance value R S0 of the cell is analyzed by alternating current impedance measurement. The conditions for the alternating current impedance measurement are a temperature of 25°C, a voltage of 10 mV, and a frequency of 7 MHz - 100 mHz.
[0057] Next, measure the initial current value I0 immediately after applying a constant voltage V to the cell, and calculate the initial resistance value R0 of the cell according to the following formula A. R0 = V / I0 ··· A The measurement conditions for the initial current value are a voltage of 10 mV, a total time of 6 seconds, and a measurement interval of 0.0002 seconds.
[0058] Resistance value R S0 And substitute the initial resistance value R0 into the following formula B to obtain the interfacial resistance R INT R INT = R0 - R S0 ··· B Next, measure the current value I after applying a constant voltage V to the cell until it reaches a steady state, and calculate the resistance value R P R P = V / I ··· C The measurement conditions for the current value in the steady state are a voltage of 10 mV, a total time of 10 hours, and a measurement interval of 60 seconds.
[0059] After the cell reaches a steady state, analyze the resistance value R S of the cell by alternating current impedance measurement under the above-mentioned conditions. Resistance value R S , resistance value R P and interfacial resistance R INT Substitute into the following formula D to calculate the transference number t Li t Li = R S / (R P - R INT ) ··· D In the electrolyte layer 14 (electrolyte composition), the amount (volume %) of the binder with respect to the combined amount of the oxide 18 and the ionic liquid is preferably 10 volume % or less (excluding 0 volume %). That is, the combined amount of the oxide and the ionic liquid: the amount of the binder = (100 - Y):Y, where 0 < Y ≤ 10. This is to ensure the formability of the electrolyte layer 14 by the binder and to reduce the decrease in the ionic conductivity of the electrolyte layer 14. The content (volume %) of the binder can be specified from the area % of the cross-section of the electrolyte layer 14 determined by analysis using SEM-EDS as described above.
[0060] The negative electrode layer 15 is formed by stacking a current collecting layer 16 and a composite layer 17. The current collecting layer 16 is a conductive member. Examples of the material of the current collecting layer 16 include a metal selected from Ni, Ti, Fe, Cu, and Si, an alloy containing two or more of these elements, stainless steel, and a carbon material.
[0061] The composite layer 17 includes an active material 20 and an electrolyte composition. The electrolyte composition includes an oxide 18. To reduce the resistance of the composite layer 17, the composite layer 17 may include a conductive additive. Examples of the conductive additive include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag. The active material 20 is Li, Li-Al alloy, Li4Ti5O 12 Examples of the material include graphite, In, Si, a Si-Li alloy, and SiO. As with the electrolyte layer 14, the composite layers 13 and 17 may contain a binder.
[0062] The secondary battery 10 is manufactured, for example, as follows. A mixture of an ionic liquid in which an electrolyte salt is dissolved and an oxide 18 is mixed with a solution in which a binder is dissolved in a solvent to make a slurry. After tape casting, the mixture is dried to obtain a green sheet (electrolyte sheet) for the electrolyte layer 14.
[0063] A mixture of an ionic liquid in which an electrolyte salt is dissolved and an oxide 18 is mixed with an active material 19, and then a solution in which a binder is dissolved in a solvent is mixed to make a slurry. After tape casting on the current collecting layer 12, it is dried to obtain a green sheet (positive electrode sheet) for the positive electrode layer 11.
[0064] A mixture of an ionic liquid in which an electrolyte salt is dissolved and an oxide 18 is mixed with an active material 20, and then a solution in which a binder is dissolved in a solvent is mixed to make a slurry. After tape casting on the current collecting layer 16, it is dried to obtain a green sheet (negative electrode sheet) for the negative electrode layer 15.
[0065] After the electrolyte sheet, the positive electrode sheet, and the negative electrode sheet are cut into a predetermined shape, they are stacked in this order, the positive electrode sheet, the electrolyte sheet, and the negative electrode sheet, and are pressure-bonded together to form an integrated unit. Terminals (not shown) are connected to the current collecting layers 12 and 16, respectively, and the unit is sealed in a case (not shown), to obtain a secondary battery 10 including a positive electrode layer 11, an electrolyte layer 14, and a negative electrode layer 15, in that order. EXAMPLES
[0066] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0067] (Preparation of oxide) Li 6.95 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 Li2CO3, MgO, La(OH)3, SrCO3, and ZrO2 were weighed out so that the total amount was as follows: Li2CO3 was used in excess of about 15 mol% in elemental terms, taking into account the volatilization of Li during firing. The weighed raw materials and ethanol were placed in a nylon pot together with zirconia balls, and ground and mixed in a ball mill for 15 hours. The slurry was removed from the pot, dried, and then pre-fired (at 900°C for 1 hour) on an MgO plate. The pre-fired powder and ethanol were placed in a nylon pot, and ground and mixed in a ball mill for 15 hours.
[0068] The slurry taken out of the pot was dried, then poured into a die with a diameter of 12 mm and pressed to obtain a green body with a thickness of about 1.5 mm. 2 The compact was then covered with calcined powder of the same composition as the compact and sintered in a reducing atmosphere (at 1100°C for 4 hours) to obtain a sintered oxide body. The lithium ion conductivity of the sintered body determined by the AC impedance method was 1.0×10 -3The lithium ion conductivity was measured under the conditions of a temperature of 25°C, a voltage of 10 mV, and a frequency of 7 MHz to 100 mHz. The sintered body was crushed in an Ar atmosphere and sieved through a sieve with a mesh size of 250 μm, and the oxide powder that passed through the sieve was collected.
[0069] 100 g of the powder that passed through the sieve, 536 g of 4 mm diameter balls, and 250 mL of fluorine-based inert liquid were placed in a pot, and the powder was ground for 6 hours using a planetary ball mill (rotation speed: 200 rpm). The slurry removed from the pot was dried to obtain a crude oxide powder.
[0070] Similarly, 50 g of the sieved powder, 536 g of 4 mm diameter balls, and 100 mL of fluorine-based inert liquid were placed in a pot, and the powder was ground for 4 hours in a planetary ball mill (rotation speed: 300 rpm). The slurry removed from the pot was dried to obtain a fine powder of the oxide.
[0071] (Heat treatment of coarse and fine powders) Tube furnace (volume 1875 cm 3 Coarse oxide powder (40 g or less) contained in a tube furnace was heated at 670 °C for 2 hours with nitrogen gas (flow rate 10 L / min) introduced from one end of the tube furnace and exhausted from the other end of the furnace. After the temperature inside the furnace reached 50 °C, the heat-treated coarse powder was immediately removed from the furnace and placed in a sealed container to prevent exposure to the atmosphere. Fine oxide powder was also heat-treated under the same conditions and placed in a sealed container.
[0072] (Measurement of particle size distribution) The particle size distribution of the heat-treated coarse powder, heat-treated fine powder, and non-heat-treated coarse powder was measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EX II). The sample to measure the particle size distribution was placed in a solvent (0.2 wt% sodium hexametaphosphate aqueous solution), dispersed for 3 minutes using an ultrasonic disperser (Nihon Seiki Seisakusho SD-600), and set in the measuring device. The refractive index of the sample was set to 1.81, the refractive index of the solvent was set to 1.33, and the D 10 ,D 50 ,D 90 ,D 100 was calculated. D50 ,D 90 are the particle sizes at which the integrated frequency (under the sieve) in the particle size distribution is 50% and 90%, respectively.
[0073] D of heat-treated coarse powder (hereinafter referred to as "Powder A"), heat-treated fine powder (hereinafter referred to as "Powder B"), and non-heat-treated coarse powder (hereinafter referred to as "Powder C") 10 The average particle diameters were 3.6 μm, 1.4 μm, and 0.5 μm, respectively.
[0074] (Preparation of electrolyte) The ionic liquid 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) was mixed with 3 mol / dm electrolyte salt LiN(SO2F)2. 3 The electrolyte was obtained by compounding.
[0075] Example 1 Powder A and the electrolyte were mixed in a mortar in an Ar atmosphere so that the oxide: electrolyte ratio was 61:39 (volume ratio) to obtain a composite powder. 18 g of the composite powder, 0.864 g of polyvinylidene fluoride (PVDF), and 7.776 g of propylene carbonate (PC) were mixed in an Ar atmosphere to obtain the slurry in Example 1.
[0076] Example 2 A slurry in Example 2 was obtained in the same manner as in Example 1, except that propylene carbonate was replaced with dimethyl carbonate (DMC).
[0077] Example 3 A slurry in Example 3 was obtained in the same manner as in Example 1, except that Powder A was replaced with Powder B.
[0078] Example 4 A slurry in Example 4 was obtained in the same manner as in Example 3, except that propylene carbonate was replaced with dimethyl carbonate.
[0079] Comparative Example 1 A slurry in Comparative Example 1 was obtained in the same manner as in Example 1, except that Powder A was replaced with Powder C.
[0080] Comparative Example 2 A slurry in Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that propylene carbonate was replaced with dimethyl carbonate.
[0081] Comparative Example 3 A slurry in Comparative Example 3 was obtained in the same manner as in Example 1, except that propylene carbonate was replaced with N-methyl-2-pyrrolidone (NMP).
[0082] (Test Method and Results) The slurries in the examples and comparative examples were each placed in a beaker and left in a container in an Ar atmosphere at 25°C for 12 hours. After 12 hours had passed, it was visually confirmed whether the slurry had gelled (become non-fluidized). The results are shown in Table 1. Slurries in which at least a part had gelled were marked with +, and slurries in which no gelling had occurred at all were marked with -.
[0083] [Table 1]
[0084] As shown in Table 1, the slurry in Example 1-4 did not gel at all, but the slurry in Comparative Example 1-3 gelled, and the slurry in Comparative Example 1-3 turned brown.
[0085] The slurries of Examples 1-4 and Comparative Examples 1 and 2 contained aprotic and protophilic polar solvents, PC and DMC. Comparing Examples 1-4, in which PC or DMC is contained in the slurry, with Comparative Examples 1-2, D 10 The slurry of Example 1-4, which contains oxides having a diameter of 1.4 μm or more, does not gel. 10 The slurries of Comparative Examples 1 and 2, which contained oxides with a diameter of 0.5 μm, gelled. The discoloration and gelling of the slurries are presumably due to the polyenation of vinylidene fluoride caused by the desorption of HF.10 It is presumed that the oxides with a size of 1.4 μm or more have a weaker basicity, which makes it difficult for the components of the slurry to interact with each other, and therefore gelation does not occur.
[0086] The slurry of Comparative Example 3 contained NMP, a protophilic polar solvent. 10 Comparing Examples 1 and 2, in which the slurry contains an oxide having a diameter of 3.6 μm, with Comparative Example 3, the slurries in Examples 1 and 2, in which aprotic and protophilic polar solvents (PC, DMC) were included, did not gel, whereas the slurry in Comparative Example 3, in which a protophilic polar solvent (NMP) was included, gelled. It is presumed that the aprotic and protophilic polar solvent is weakly basic compared to the protophilic polar solvent, so that interaction between the components of the slurry is less likely to occur, and therefore gelation did not occur.
[0087] According to this embodiment, a garnet-type oxide containing Li, La and Zr is used. 10 It has been revealed that an electrolyte composition containing an oxide having a particle size of 1.4 μm or more, an ionic liquid containing an imidazolium cation and a sulfonylimide anion, an electrolyte salt, a binder containing a vinylidene fluoride-based polymer, and an aprotic and protonic polar solvent can reduce gelation. An electrolyte sheet and a secondary battery containing this electrolyte composition can reduce the variation in the dispersion state of the components, thereby reducing the variation in performance.
[0088] The present invention has been described above based on an embodiment, but the present invention is not limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.
[0089] In the embodiment, the secondary battery 10 has been described as including the positive electrode layer 11 having the composite layer 13 provided on one side of the current collecting layer 12, and the negative electrode layer 15 having the composite layer 17 provided on one side of the current collecting layer 16, but the present invention is not necessarily limited to this. For example, it is naturally possible to apply each element in the embodiment to a secondary battery including an electrode layer (so-called bipolar electrode) having the composite layer 13 and the composite layer 17 provided on both sides of the current collecting layer 12, respectively. If the bipolar electrodes and the electrolyte layer 14 are alternately stacked and housed in a case (not shown), a so-called bipolar structure secondary battery can be obtained.
[0090] In the embodiment, the case where the composite layers 13, 17 and the electrolyte layer 14 all contain the electrolyte composition has been described, but this is not necessarily limited to this. It is sufficient for at least one of the composite layers 13, 17 and the electrolyte layer 14 of the secondary battery to contain the electrolyte composition.
[0091] In the embodiment, the secondary battery 10 including the electrode layers (positive electrode layer 11 and negative electrode layer 15) and the electrolyte layer 14 has been described by taking a lithium ion battery (secondary battery) containing an electrolyte composition as an example, but is not necessarily limited thereto. Other examples of secondary batteries include a lithium-sulfur battery, a lithium-oxygen battery, and a lithium-air battery. [Explanation of symbols]
[0092] 10 Secondary battery 11 Positive electrode layer 14 Electrolyte layer (electrolyte sheet) 15 Negative electrode layer 18 Oxides
Claims
1. An electrolyte composition comprising an oxide having a garnet structure containing Li, La, and Zr, an electrolyte salt, an ionic liquid, a binder, and a solvent, The oxide has a particle size of 1.4 μm or more at which the integrated value of the frequency in a volume-based particle size distribution is 10%, the ionic liquid comprises an imidazolium cation and a sulfonylimide anion; the solvent is an aprotic, protophobic polar solvent, The binder is -CH 2 CF 2 - An electrolyte composition comprising:
2. An electrolyte sheet comprising the electrolyte composition according to claim 1.
3. The cathode layer, the electrolyte layer, and the anode layer are included in the stack, A secondary battery, wherein at least one of the positive electrode layer, the electrolyte layer, and the negative electrode layer contains the electrolyte composition according to claim 1.
Citation Information
Patent Citations
Lithium ion conductive ceramic sintered compact, and lithium battery
JP2017088420A
Power storage device
JP2021018860A
Ionic conductors and lithium batteries
JP6682708B1
Electrolyte composition, secondary battery, and method for producing electrolyte sheet
WO2018220800A1
Slurry composition for batteries, and methods for producing electrode, electrolyte sheet, and battery member
WO2020240786A1